EFFECT OF LEAF SPRAY TREATMENTS ON ROOTING AND QUALITY OF Prunus mahaleb (L.) CUTTINGS - Veronika Szabó; Lajos Magyar; Károly Hrotkó (Acta Scientiarum Polonorum: Hortorum Cultus, 2016)
Cuttings are exposed to several stress factors during rooting. Leaf nutrient sprays may compensate the stress. Six treatments of leaf fertilizers and biostimulators and BA were applied on rooting two cultivars of Prunus mahaleb cuttings. Cuttings were taken from untreated stockplants in late May. Each cutting was 20 cm long with three leaves each cut in half. On all cuttings’ base, except for untreated ones, 0.2% IBA were applied by dipping in 50% ethanol solution, than inserted into perlite and rooted under intermittent mist. The following leaf spray treatments were applied weekly on rooting cuttings from the first to fourth week: Kelpak® 0.2%, Wuxal® Ascofol 0.2%, Pentakeep®-V 0.05%, Yeald Plus® 0.15%, early BA 0.2%. The later BA treatment started on the 4th week of rooting. Control was sprayed with tap water. Yeald Plus® and Pentakeep®-V show some improving tendency in rooting rate compared to IBA treated and control (8.9 and 4.0%) on ʽBogdány’ in average of three years. On ʽMagyar’ cuttings, which can be characterized with low rooting potential, foliar sprays of Kelpak®, Wuxal® Ascofol, Pentakeep ®-V and Yeald Plus® significantly increased the rooting rate and the fresh weight increment during the rooting, while Pentakeep®-V and Yeald Plus® significantly increased the total dry weight of rooted cuttings.